A Study of Chemical Content in Some Species of Tribe Apieae / Apiace - Muhammad, Zahra B.; Al-Khesraji, Talib O. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this study, the flavonoid and alkaloid content in the alcoholic extract of the shoots and flowers were identified in four species of the tribe Apieae / Apiacese : Ammi majus, Ammi visgana, Anethum graveolens and Foeniculum vulgaris, and the flavonoids that were detected are (Apigenin, Coumarin, Kaempferol and Quercetin). The species Foeniculum vulgaris has recorded the highest concentration of total flavonoid content (Shoots and Flowers) among the studied species, reaching 4139.2 Âµg / ml. The total alkaloids are estimated for these species, and the Foeniculum vulgaris has recorded the highest concentration of the total alkaloid content as well.